Transdermal Drug Delivery System - A Novel Drug Delivery System and its Market Scope and Opportunities - K.P.SAMPATH KUMAR,; DEBJIT BHOWMIK,; CHIRANJIB.B,; R.M.CHANDIRA, (International Journal of Pharma and Bio Sciences, 2010)
As a substitute for the oral route Transdermal drug delivery enables the avoidance of gastrointestinal absorption, with its associated pit falls of enzymatic and pH associated deactivation. Transdermal delivery has many advantages over conventional modes of drug administrations, it thus avoids hepatic first pass metabolism and improves patient compliance. This approach of drug delivery is more permanent in case chronic disorders like hypertension which requires long term dosing to maintain therapeutic drug concentration. These systems are easy to apply and remove as when desired. In Intensive research has shown that Transdermal route is a potential mode of delivery of lipophilic drugs in systemic circulation. The market for Transdermal devices is currently estimated at US$ 1.2 billion, approximately 10% of the entire US $ 28 billion drug delivery market. In addition, Transdermal drug delivery market is currently based on only 10 drugs. Hence, Pharmaceutical scientists are striving to add new deliverables to the short list of approved Transdermal products. This proposed method also allows for reduce therapeutic dosaging due to the shortened metabolization pathway of the Transdermal route versus the gastrointestinal pathway. The main aim and objective of Transdermal drug delivery system are topical administered medicaments in the form of patches that deliver drugs for systemic effect at a predetermined and controlled rate. Transdermal systems deliver drugs direct through the skin. Worldwide market revenues for transdermal drug delivery systems are at US$3 billion with the growth rate expected to increase 12% annually through 2007. The market value for transdermal delivery was $12.7 billion in 2005 and it is expected to increase to $21.5 billion in the year 2010 and $31.5 billion in the year 2015.